Investment under company-level pacts - Lutz Bellmann; Hans-Dieter Gerner; Olaf Hübler (Institute for the Study of Labor (IZA), 2013)
To improve their competitiveness the companies aim to increase the funds available to finance the necessary investments. In order to reduce wage costs company-specific deviations from industry-level wage contracts are concluded. Company-level pacts between the management and the works council are often preferred in comparison to agreements between employers' association and unions because the former negotiating partners are better informed about the economic situation of a company and have less goal conflicts than the latter. Moreover, these company-level pacts might reduce the hold-up problems which arise once specialized investment is made. Therefore, this paper investigates whether such agreements affect firm-level investment. Based on the IAB Establishment Panel Survey 2001-2010 our estimates reveal that the adoption of a company-level pact leads to a higher investment rate than in other firms driven by re-investment. However, the Great Recession has damped this positive influence. From our econometric analysis we cannot detect any increase in investment during the negotiation phase. After the expiration of a CLP, lower reinvestment and a small increase in net investment take place. Furthermore, our econometric results show that the company-level pacts' success depends on the specific measures which are agreed and on the duration of the pacts.
Keywords: J50; J52; J53; D24; 330; industrial relations; pacts for employment and competitiveness; investments